SPATIAL DIFFERENTIATION OF GLOBAL SOLAR RADIATION IN TORUŃ AND ITS SUBURBAN AREA (CENTRAL POLAND) IN 2012 - KEJNA, MAREK; USCKA-KOWALKOWSKA, JOANNA; ARAŹNY, ANDRZEJ; KUNZ, MIECZYSŁAW; MASZEWSKI, RAFAŁ; PRZYBYLAK, RAJMUND (Bulletin of Geography. Physical Geography Series, 2015)
This article investigates the spatial distribution of global solar radiation (K↓) in Toruń and its suburbs, observed in 2012. Measurements were taken at 12 points (7 within the city and 5 in the suburban area) using CNR4 net radiometers and automatic weather stations (Vantage Pro+). At all locations, the diurnal and annual courses of K↓ were typically related to the Earth’s rotational movement and changes in the sun’s declination over the year, and disturbed by clouds and atmospheric phenomena that enhance the extinction of solar radiation. A substantial spatial diversity of K↓ was observed in Toruń and its suburbs. The annual sum of K↓ at several urban locations accounted for over 70% of the solar radiation in the open space outside the city. The amount of incoming solar radiation in the urban area was more restricted in winter (<50%) than in summer (approx. 70%). The diurnal courses of K↓ were heavily disturbed by local obstacles which cast shadows (causing a considerable decrease of K↓), but there were instances of increases in K↓ (122%) augmented by radiation reflected from roofs, walls and windows surrounding the measurement point. The spatial diversity of K↓ in the urban area is heterogeneous, due to local meteorological conditions (cloudiness, fog, smog and airborne dust) and the obscuring of the horizon.